Mechanical Properties and Dry–Wet Stability of Soda Residue Soil - Xiaoqing Zhao; Tianfeng Yang; Teng Liang; Zhongling Zong; Jiawei Li (Buildings, 2023)
To effectively utilize the effectively the solid waste-soda residue (SR) and fly ash (FA), a mixture of 70% SR, 20% FA, and 10% clay was formed to produce soda residue soil (SRS). By adding cement and/or lime, four different SRS proportions were prepared. The compaction properties, mechanical properties, and dry–wet stability. Furthermore, the mechanical mechanisms of SRS were explored, and the improvement effect and efficiency of cement and/or lime on the mechanical performance of SRS were analyzed. The results show that the SRS is lightweight and easy to compact and shape, which is conducive to construction. Compared to cement, lime has a greater impat on the compaction properties of SRS. The mechanical properties of SRS are enhanced after adding cement and/or lime; the unconfined compressive strength (UCS), California Bearing Ratio (CBR), and resilient modulus all increase significantly. The UCS, CBR, and resilient modulus of SRS with different proportions all increase with the increase of compaction degree; the CBR and resilient modulus can meet the requirements of the subgrade, and the UCS can meet the requirements of the base and sub-base. The contribution rate of cement per unit amount is better than that of lime to the mechanical performance of SRS. As dry–wet cycles increase, the dry–wet stability of SRS with different proportions first increases and then decreases, which is affected by hydration and dry–wet deterioration together, with a critical cycle number for the strength transition. The excellent mechanical performance of SRS benefits from the gradation and chemical action. The particles of SR, FA, and clay can complement each other and perform an interlocking action. Therefore, SRS has a good gradation and forms a dense and stable structure. Also, the chemical reactions between materials are very important. The cement and/or lime have a hydration and gelling effect, FA and clay participate in pozzolanic reactions, and SR and FA have certain alkali-activated effects.